(untitled) (Bangladesh Journal of Nuclear Medicine, 2025)
Objectives: This retrospective study was performed to show population trends of gated stress myocardial perfusion imaging (MPI) using single photon emission computed tomography (SPECT) describing sociodemographic and clinical variables of the patients in a tertiary center, the National Institute of Cardiovascular Disease (NICVD). Patients and Methods: This retrospective study recruited a total of 1236 patients who underwent stress-gated SPECT MPI scans from October 2019 to October 2024 in the department of Nuclear Cardiology, NICVD, Bangladesh. Results: A total of 1236 patients were studied, with the majority of them being male (85.4%). Mean age in both genders is 52.2 years. The highest number of patients was found in the year 2023. Either pharmacological or exercise stress was given. The main indication of referral was risk stratification after old myocardial infarction (OMI) (65.2%). Major MPI findings in studied patients were fixed defect (68.7%); SVD (41.7%); DVD (32%); TVD (17.4%); high SSS in 77.3%. High-risk features found after ECG gating were a dilated left ventricular cavity (54.9%) and high TID (38.2%). Involved vascular territory in both coronary angiogram and MPI matched in 70% of cases. Conclusion: Gated stress SPECT MPI is a powerful tool for risk stratification and management of CAD patients, and the Nuclear Cardiology department of NICVD is serving the Bangladeshi population on a wide scale in this regard. Bangladesh J. Nuclear Med. 28(1): 81-86, 2025